The role of vascular biomarkers for primary and secondary prevention. A position paper from the European Society of Cardiology Working Group on peripheral circulation: Endorsed by the Association for Research into Arterial Structure and Physiology (ARTERY) Society - Vlachopoulos, Charalambos; Xaplanteris, Panagiotis; Aboyans, Victor; Brodmann, Marianne; Cífková, Renata; Cosentino, Francesco; De Carlo, Marco; Gallino, Augusto; Landmesser, Ulf; Laurent, Stéphane; Lekakis, John; Mikhailidis, Dimitri P; et al. (Atherosclerosis, 2015)
While risk scores are invaluable tools for adapted preventive strategies, a significant gap exists between predicted and actual event rates. Additional tools to further stratify the risk of patients at an individual level are biomarkers. A surrogate endpoint is a biomarker that is intended as a substitute for a clinical endpoint. In order to be considered as a surrogate endpoint of cardiovascular events, a biomarker should satisfy several criteria, such as proof of concept, prospective validation, incremental value, clinical utility, clinical outcomes, cost-effectiveness, ease of use, methodological consensus, and reference values. We scrutinized the role of peripheral (i.e. not related to coronary circulation) noninvasive vascular biomarkers for primary and secondary cardiovascular disease prevention. Most of the biomarkers examined fit within the concept of early vascular aging. Biomarkers that fulfill most of the criteria and, therefore, are close to being considered a clinical surrogate endpoint are carotid ultrasonography, ankle-brachial index and carotid-femoral pulse wave velocity; biomarkers that fulfill some, but not all of the criteria are brachial ankle pulse wave velocity, central haemodynamics/wave reflections and C-reactive protein; biomarkers that do no not at present fulfill essential criteria are flow-mediated dilation, endothelial peripheral arterial tonometry, oxidized LDL and dysfunctional HDL. Nevertheless, it is still unclear whether a specific vascular biomarker is overly superior. A prospective study in which all vascular biomarkers are measured is still lacking. In selected cases, the combined assessment of more than one biomarker may be required.
Keywords: Research Design; Europe; arteriae carotides; biologické markery; C-Reactive Protein; Carotid Intima-Media Thickness; Biomarkers; ultrasonografie; výsledek terapie; Decision Making; primární prevence; Ankle-brachial index; Vascular biomarkers; Aging; Central haemodynamics; Hemodynamics; Primary Prevention; hemodynamika; lidé; tlakový index kotník-paže; Wave reflections; Evropa; analýza nákladů a výnosů; Ankle Brachial Index; Ultrasonography; tuhost cévní stěny; Treatment Outcome; společnosti lékařské; Arterial stiffness; intimomediální šíře tepenné stěny; Endothelial function; Societies, Medical; sekundární prevence; Carotid Arteries; Secondary Prevention; Cardiovascular Diseases; rozhodování; kardiologie; riziko; stárnutí; Cardiology; Circulating biomarkers; kardiovaskulární nemoci; C-reaktivní protein; Carotid ultrasonography; Risk; Vascular Stiffness; výzkumný projekt; Cost-Benefit Analysis; Humans